Plasma D-Dimer Level in Different Types of Acute Ischaemic Stroke Patients: Experience at a Tertiary Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Plasma D-Dimer is a biomarker of thrombo-embolism.Objective: The purpose of the present study was to see the plasma D-dimer level in different types of acute ischaemic stroke patients.Methodology: This cross-sectional study was conducted in the Department of Neurology & Department of Internal Medicine at Dhaka Medical College Hospital, Dhaka, Bangladesh from July 2010 to June 2012 for a period of two (02) years. Patients with ischemic stroke with history within 7 days attending in the stroke clinic of Department of Neurology or admitted in the Department of Neurology and Internal Medicine through the outpatient and emergency Department of Dhaka Medical College Hospital (DMCH) were selected as study population for this study. Analysis of plasma D-Dimer was done in the Department of Hematology of DMCH.bResult: A total of 50 cases were recruited for this study. There were 24.0% lacunar infarcts, 40.0% atherothrombotic and 36.0% embolic infarcts in the study group. Highest level of plasma D-Dimer was observed in embolic (1700±964 ηg/ml) followed by atherothrombotic group (536±234 ηg/ml). The plasma D-Dimer was lowest (100±0 ηg/ml) in lacunar group. Concentration of Plasma D-Dimer showed significant correlation with clinical diagnosis in different subtypes of ischemic stroke (r=0.902; p=0.001) and also with risk factors, example, diabetes (r=0.319; p=0.012) and valvular heart disease (r=0.281; p=0.024), but no significant correlation with age, hypertension, hyperlipidaemia and smoking.Conclusion: In conclusion plasma D-Dimer is an important bio-marker in the clinical diagnosis and subtypes of ischemic stroke patients.Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 13-17